Politics of Indigeneity in Fogarty's Poetry - Gorman, Sean (Purdue University Press, 2011)
In his article "Politics of Indigeneity in Fogarty's Poetry" Sean Gorman discusses Indigenous themes and issues with regards to the poetry of Murri writer Lionel Fogarty. As Fogarty is seen as a poet who writes complex prose, his material challenges non-Indigenous readerships by subverting Standard English and conventional reading practices. Gorman suggests strategies by which to engage with Fogarty's material and, employing the theories of Mikhail Bakhtin, namely heteroglossia and dialogism, to arrive at a better understanding of the rich and complex nature of Fogarty's work. Gorman executes his analysis in relation to the political debates that have arisen since the Little Children Are Sacred report was made public and the intervention in Australia's Northern Territory occurred in 2007.